Effect of Different Modelling Assumptions on the Seismic Response of RC Structures - Sousa, Romain (2020)
The introduction of new regulations for seismic assessment of structures established stricter performance requirements for existing buildings. In order to account for the poor seismic behaviour of such buildings, recent seismic codes, namely Eurocode 8 (EC8), introduce a number of prescriptions regarding issues such as analysis type, load distribution, accidental eccentricity, etc. At the same time, these codes give room for engineering judgment to be used with reference to the definition of structural and non-structural elements such as slabs or infill walls, and obviously leave the modelling assumptions, such as Finite Elements typology, meshing, mass modelling, etc. to the analyst decision. As such, four existing RC buildings, representative of traditional Mediterranean construction, considering different modelling assumptions, were subjected to an extensive number of nonlinear static analyses. The interpretation of possible deviations in the results will hopefully provide indications on the relative importance of each modelling parameter or decision.